2020
DOI: 10.37496/rbz4920200035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation with β-hydroxy-β-methylbutyrate on stress parameters in goat kids

Abstract: The objective of this study was to determine the effect of dietary supplementation with β-hydroxy-β-methylbutyric acid (HMB) on live weight loss and selected blood parameters in goat kids after transportation to the slaughterhouse. The study was performed with goat kids that were weaned at 30 days of age and divided into two groups (GK): a control group and an experimental group whose diet was supplemented with HMB (at 50 mg kg −1 of BW) for 60 consecutive days. At the end of the 90-day rearing period, the ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…These findings are in consistent with a previous study by Tajik et al (2016) reported that no significant difference between two sexes of Raini goats in glucose level after transport. However, regardless of sexes, this finding is similar with previous studies, which is increased glucose after transport (Minka and Ayo, 2014;Sowińska et al, 2020;Raghazli et al, 2021). Minka and Ayo (2014) reported that a significant increase in glucose levels on goats after 12 hours transport with total distance about 600 km.…”
Section: Biochemical Parameters Serumsupporting
confidence: 91%
See 3 more Smart Citations
“…These findings are in consistent with a previous study by Tajik et al (2016) reported that no significant difference between two sexes of Raini goats in glucose level after transport. However, regardless of sexes, this finding is similar with previous studies, which is increased glucose after transport (Minka and Ayo, 2014;Sowińska et al, 2020;Raghazli et al, 2021). Minka and Ayo (2014) reported that a significant increase in glucose levels on goats after 12 hours transport with total distance about 600 km.…”
Section: Biochemical Parameters Serumsupporting
confidence: 91%
“…There also have been reported that no significant difference between two sexes in serum concentration of cortisol (Tajik et al, 2016). However, regardless of sexes, previous studies have reported similar findings, with increased cortisol concentration observed in goats after transport (Alcalde et al, 2016;Tajik et al, 2016;Mir et al, 2018;Sowińska et al, 2020). This result is contrary to previous studies, where no differences (Raghazli et al, 2021), were observed in goats prior to and after transport.…”
Section: Cortisolmentioning
confidence: 62%
See 2 more Smart Citations